The Contribution of A. I. in Pharmaceutical Software - Mohd. Wasiullah; Piyush Yadav; Vikash Yadav; Rajan Yadav (International Journal of Biomedical Innovations and Engineering, 2025)
The integration of Artificial Intelligence (AI) in pharmaceutical software has significantly transformed drug development, regulatory processes, and clinical management. AI-powered tools are revolutionizing data analysis, predictive modeling, and decision-making, enhancing the efficiency and accuracy of drug discovery and development. This article explores the multifaceted contributions of AI to pharmaceutical software, including its applications in drug screening, personalized medicine, clinical trial optimization, and regulatory compliance. Additionally, we examine how AI is improving the management of patient data, optimizing supply chain processes, and supporting the development of new therapeutic solutions. The article delves into the challenges and ethical dilemmas of integrating AI into the pharmaceutical industry, stressing the importance of transparent practices, safeguarding data privacy, and ensuring thorough validation. This review seeks to present a snapshot of AI’s current role and prospects in pharmaceutical software, shedding light on how these innovations are transforming healthcare and medicine.
Keywords: Computer system software; GMP practices; healthcare and medicine; product quality; regulatory agency requirements